Folklore And Animals In Le Collège Noir - Belazouz Asma (University of Eloued جامعة الوادي, 2025)
This paper explores the visual and narrative representations of animals in the comic Le Collège Noir. It investigates the folkloric dimension of the storyworld that balances between folkloric stability and variability. By depicting animals as cunning, wise, and at times evil, the narrative preserves the image of the archetypal animal with anthropomorphic characteristics. In doing so, the comic books and their adaptive revision create a space where everything is possible for a quest to be undertaken. The interplay between folklore, mystery, and wisdom in a detective-like narrative calls for animals to unveil hidden truths and unlock buried secrets. The transmedial approach allows for the study to cross mediums, times, and genres to highlight the interwoven narrative and visual elements that imagine together animal characters capable of reciprocating human mystery and wisdom.
Article . Ex Professo. Vol. 10. N1
Keywords: Animal characters; Comics; Folkloresque; Le Collège Noir; Storyworld